Nutrients for sugar beet production: soil-plant relationships - Draycott, A. Philip (Arthur Philip); Christenson, Donald R (CABI Publishing, 2003)
After a summary of world sugar production from beet the authors cover the plant's need of each macro and micronutrient and effects on growth, yield and crop quality. The soil's supply of nutrients is examined as the basis for use of mineral fertilizers, organic manures and foliar applications. The book provides an up-to-date review of relevant research and the authors draw out practical guidelines so that all concerned with growing the crop can make use of this latest information. The book is destined to become the standard reference on the subject for many years to come. It represents the only significant work in English since Dr Draycott's earlier title on the same subject, published 30 years ago.